The tasting organ of domestic dogs (Canis lupus familiaris Linnaeus, 1758) - Massari, Catia Helena de Almeida Lima; Barbosa, Laleska; Resende, Henrique Ribeiro Alves de (Pubvet, 2021)
This literature review aims at describing the tasting organ anatomy of dogs, because although so much is publicized about the palatability applied to animal nutrition, little is known about the anatomical structures intended for food flavors perception. The tongue is the organ in which most receptors are found for sense of taste, and the taste buds are microscopic structures associated with the fungiform, foliated and vallate papillae of the canine lingual mucosa. The gustatory pathway, constituted by a sequence of three types of neurons, connects lingual receptors to the central portion of the nervous system, allowing the animal to perceive and respond to stimuli. It is concluded that the factors described in the present work must be considered in the industrial feed manufacturing process, in order to enable dogs pleasure to feed, contributing to animal welfare.
Keywords: Esthesiology; veterinary medicine; animal nutrition; sense organs; gustatory pathway